2023
DOI: 10.31083/j.rcm2403064
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Value of Exaggerated Blood Pressure Response to Exercise

Abstract: The hypertensive response to exercise testing, defined as exaggerated blood pressure response (EBPR), has been documented to be independently associated with unhealthy conditions, carrying an increased risk of future hypertension, cardiovascular (CV) morbidity and mortality. In treated hypertensives, EBPR is a marker of uncontrolled hypertension, a condition previously undetected by office blood pressure (BP) measurements at rest; EBPR may also detect masked hypertension, a phenotype characterized by normal BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
1
0
1
Order By: Relevance
“…It is known that individuals, even those with normal BP at rest, may show an exaggerated BP response during exercise. [25] Two previous studies demonstrated both higher SBP and DBP with low-intensity BFR cycling performed at an intensity corresponding to 40% of maximal oxygen consumption or 40% of peak power in healthy subjects. [6–10] One of these studies compared BP during 2-minute bouts of cycling (40% of peak power) in BFR and BFF conditions and found that both SBP and DBP increased during all training bouts.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that individuals, even those with normal BP at rest, may show an exaggerated BP response during exercise. [25] Two previous studies demonstrated both higher SBP and DBP with low-intensity BFR cycling performed at an intensity corresponding to 40% of maximal oxygen consumption or 40% of peak power in healthy subjects. [6–10] One of these studies compared BP during 2-minute bouts of cycling (40% of peak power) in BFR and BFF conditions and found that both SBP and DBP increased during all training bouts.…”
Section: Discussionmentioning
confidence: 99%
“…Vários estudos e meta-análises revelaram que a RHE pode tentar definir-se ao longo de um amplo intervalo de valores que tornam quase impossível encontrar uma solução única de compromisso operacional que satisfaça a maioria das situações da prática clínica. [13][14][15][16][17] As recomendações da American Heart Association 18 O estudo de 1 876 atletas olímpicos, normotensos e saudáveis, com idade média de 25 ± 6 anos, indicou valores limite para a PA de 225/90 mmHg em ambos os sexos. 20 Um pequeno subconjunto desta população de atletas (7.5%) excedeu esses limites sem apresentar correlação clínica sugestiva de hipertensão ou qualquer outra condição patológica.…”
Section: Introductionunclassified